Pemberdayaan Masyarakat melalui Peningkatan PHBS dalam Upaya Pencegahan Stunting di Dusun Waralohi - Epi Dusra; Ety Dusra; Edi Sugiarto; Agustio Kolyaan (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Stunting isaa chronicanutritional problemathat remains a major publicahealth challengeain Indonesia, aincluding inaSeram Bagian Barat District. aOne ofathe risk factors for stuntingaamong children under five is thealow implementationaof Cleanaand HealthyaLiving Behaviora (PHBS) within families and communities. Therefore, this communityaservice programawas carriedaout withathe aimaof improving community knowledge, attitudes, and practices related to PHBS asaan effortato preventastunting inachildren underafive. The implementation methods included health education through interactive counseling, agroup discussions, aand demonstrationsaof PHBSapractices, particularly handwashingawith soap. The program was attended by 30 community menbers, most of whom were mothers with infants and young children. Coordination, collaboration, and theainvolvement ofaboth internalaand externalastakeholders, particularly the head of Waralohi Hamlet, playedaan importantarole in the success of this program. Evaluation results indicated anaincrease inaparticipants’ knowledge and understandingaof PHBS and its relevance to stunting prevention. In addition, the program was considered beneficial due to the appropriate selection of location, high participant enthusiasm, and a conducive implementation atmosphere. In conclusion, the PHBS strengthening program proved effective in raising community awareness to adopt healthy living behaviors that support effortsato preventastunting inachildren underafive.